Cover Image, Volume 170A, Number 12, December 2016. Issue 12 (December 2016) - Takenouchi, Toshiki; Yoshihashi, Hiroshi; Sakaguchi, Yuri; Uehara, Tomoko; Honda, Masataka; Takahashi, Takao; Kosaki, Kenjiro; Miyama, Sahoko
Abstract : The cover image, by Toshiki Takenouchi et al., is based on the Clinical Report Hirschsprung disease as a yet undescribed phenotype in a patient with ARID1B mutation, DOI:10.1002/ajmg.a.37861 .